2018
DOI: 10.1039/c8ra00095f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced physical properties of γ-Al2O3–rGO hybrids prepared by solvothermal and hot-press processing

Abstract: aIn this study, a solvothermal method was employed for the first time to fabricate hybrids composed of crosslinked g-Al 2 O 3 nanorods and reduced graphite oxide (rGO) platelets. After calcination and hot-press processing, monoliths of Al 2 O 3 -rGO hybrids were obtained with improved physical properties. It was found that the oxygen-containing groups on graphene oxide were beneficial for the adsorption of aluminum isopropoxide, leading to a uniform dispersion of rGO with Al 2 O 3 , which was obtained by hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…It is assumed that attachment of indole group provides the additional surface area which facilitates the adsorption process. A similar trend was also observed by other researchers [38] , [39] . The nitrogen adsorption–desorption isotherm showed adsorption type-III and IV by non-sonicated and sonicated aluminium hybrids.…”
Section: Resultssupporting
confidence: 91%
“…It is assumed that attachment of indole group provides the additional surface area which facilitates the adsorption process. A similar trend was also observed by other researchers [38] , [39] . The nitrogen adsorption–desorption isotherm showed adsorption type-III and IV by non-sonicated and sonicated aluminium hybrids.…”
Section: Resultssupporting
confidence: 91%
“…Other works concerned a newly developed solvothermal method, which was employed for the first time to fabricate RGO/Al 2 O 3 nanocomposite in a form of Al 2 O 3 nanorods covering the GO surface ( Ikram et al, 2018 ). Further reduction of GO to RGO was obtained by further calcination treatment, which was followed by hot pressing to obtain hybrid samples.…”
Section: On the Rgo/ai 2 O 3 Nanocomposite Systemmentioning
confidence: 99%
“…Low strength and brittle attributes are the main properties of ceramics. The most widely used structural ceramic is alumina, due to its good thermal conductivity and the shape stability [7]. Alumina has a wide range of applications, some of the fields include dental implants, high speed cutting tools, chemical insulators, electrical insulators, and wear resistant coatings.…”
Section: Highly Conductive Graphene-alumina-based Hybrid Monoliths For Electrical Thermal and Mechanical Applicationsmentioning
confidence: 99%
“…Moreover, scientists have found that in a microwave preparation of alumina-rGO composites, the grain size of the alumina matrix was reduced from 475 to 180 nm, which was obtained from the conventional sintering process, leading to an increase in the Young's modulus from 148 to 180 GPa. Scientists have found that using solvothermal-hot press processing route, highly conductive alumina-rGO hybrids may be obtained, which consist of Al 2 O 3 nanorods and rGO, respectively [7,8,10]. The same solvothermal method was used to form hybrids from cross-linked Al 2 O 3 nanorods and reduced graphite oxide (rGO) platelets.…”
Section: Highly Conductive Graphene-alumina-based Hybrid Monoliths For Electrical Thermal and Mechanical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation